The Awareness of Millennial Generation Towards Halal-Certified Products: An Empirical Study Potentially Influencing Policy-Making - Artami, Ida Ayu Ketut; Maryanti, Sri; Netrawati, I Gusti Ayu Oka; Sukmana, Febrian Humaidi (Magister of Law, Faculty of Law, University of Mataram, 2023)
In addition to understanding the implementation of Law No. 30 of 2014 concerning Halal Product Assurance, this study also aims to ascertain the level of awareness among the millennial generation in Kota Mataram regarding halal-certified products and the influencing factors such as religious beliefs, exposure, and health motivations. Furthermore, the findings of this study are expected to provide insights for stakeholders in formulating more effective halal policies. The data for this research were collected from both secondary and primary sources. The primary data were obtained through the distribution of questionnaires to a sample of 152 respondents, and the data were analyzed using descriptive statistics. The results of this study indicate that the implementation of the aforementioned law is progressing adequately, albeit with some challenges. It was observed that the awareness of millennial generation in Kota Mataram towards halal-certified products is high, reaching 82%. However, there is a tendency for respondents to be uncertain about conducting pre-purchase checks on the halal status of products. The millennial generation in Kota Mataram exhibits a strong religious inclination, as evidenced by a religious belief score of 92%. Nonetheless, there appears to be a propensity for them to allocate insufficient time to enhance their understanding of religious matters. Furthermore, the millennial generation in Kota Mataram demonstrates a notable exposure (66%) to halal-certified products, although there seems to be a lack of consistent updates regarding information on products that are halal-certified. Lastly, concerning the association of health reasons with halal-certified products, an 81% response rate was recorded. However, it is evident that the millennial generation in Kota Mataram is somewhat hesitant to fully embrace the notion that halal-certified products guarantee health benefits and disease prevention.